2001
DOI: 10.1007/s001980170042
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Calcium Intake and Physical Activity on Bone Mineral Content and Bone Size in Healthy Children and Adolescents

Abstract: Studies of determinants of bone mineralization during growth are relevant to the attempt to increase peak bone mass. The aim of this study was to examine how calcium intake and physical activity influence bone size (bone area, BA), accretion in BA, whole body bone mineral content (BMC) and accretion in BMC. BA and BMC were examined by dual-energy X-ray absorptiometry (Hologic 1000/W) in healthy girls (n = 192) and boys (n = 140) aged 5-19 years at baseline and 1 year later. Calcium intake was assessed three ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 40 publications
(74 reference statements)
3
29
0
1
Order By: Relevance
“…Other cross-sectional studies described similar findings, i.e. a significant association between various bone parameters with a PA measure in boys, but not in girls [22,34]. Janz et al [17] looked at the longitudinal influence of PA (measured by accelerometers) on bone parameters in prepubertal children between the age of 5 and 8 years.…”
Section: Discussionmentioning
confidence: 54%
“…Other cross-sectional studies described similar findings, i.e. a significant association between various bone parameters with a PA measure in boys, but not in girls [22,34]. Janz et al [17] looked at the longitudinal influence of PA (measured by accelerometers) on bone parameters in prepubertal children between the age of 5 and 8 years.…”
Section: Discussionmentioning
confidence: 54%
“…However, the results of the current study were in contrast to these findings, probably due to the limited number of subjects with adequate calcium intake within the sample. A study demonstrated that there was a positive relationship between spontaneous calcium intake and bone mass in a group of children with only high intake of calcium of around 1000 to 1200 mg/day [64]. Perhaps this was why this study did not show any significant relationship between calcium and BMC.…”
Section: Discussionmentioning
confidence: 61%
“…A survey adapted from the scientific literature was conducted to determine the participants' recall of dietary calcium intake during the last 2 weeks. 24, 25 The research protocol was approved by the National Institute for Occupational Safety and Health (NIOSH) Human Subjects Review Board and the University Institutional Review Board (IRB) for human health protection. All subjects and their guardians provided written consent and assent to participate in this study.…”
Section: Subjectsmentioning
confidence: 99%